The Relationship between the Existence of Community Reading Garden Management and Community Reading Interest in TBM Anugerah, Dharmasraya Regency - Putri, Vivin Alvisa; Azizah, Zahratul (Universitas Negeri Padang, 2024)
This research is motivated by the low interest in reading among the community at TBM Anugerah in Dharmasraya Regency, which is suspected to be due to the existence of TBM Anugerah management as assessed from the aspects of collection availability, managerial competence, service facilities, and information provision. The aim of this research is to reveal (1) The description of TBM management existence; (2) The description of community reading interest; (3) To observe the relationship between TBM management existence and community reading interest at TBM Anugerah in Dharmasraya Regency. This research uses a quantitative approach with a correlational research type. The population in this study consists of 40 respondents. The sampling technique used is simple random sampling. The sample is taken from the population of 30 respondents, representing 75% of the total population. Data collection technique uses a questionnaire. Data analysis technique employs percentage formulas and product moment correlation formulas. The results of this research show that: (1) The existence of TBM Anugerah management in Dharmasraya Regency is categorized as low; (2) Community reading interest at TBM Anugerah in Dharmasraya Regency is categorized as low; (3) There is a significant relationship between management existence and community reading interest at TBM Anugerah in Dharmasraya Regency. Research recommendations are: 1) It is recommended for management to improve and develop the facilities and infrastructure management at TBM Anugerah in Dharmasraya Regency. 2) It is suggested for management to innovate to enhance community reading interest at TBM Anugerah. 3) It is hoped for future researchers to examine new variables to add and complement the existing variables.Keywords: Management Existence, Reading Interest, Community Reading Park